Tissue Non-Specific Alkaline Phosphatase and Vascular Calcification: A Potential Therapeutic Target - Azpiazu, Daniel; Gonzalo, Sergio; Villa-Bellosta, Ricardo (Current Cardiology Reviews, 2019)
Vascular calcification is a pathologic phenomenon consisting of calcium phosphate crystal deposition in the vascular walls. Vascular calcification has been found to be a risk factor for cardiovascular diseases, due to its correlation with cardiovascular events and mortality, and it has been associated with aging, diabetes, and chronic kidney disease. Studies of vascular calcification have focused on phosphate homeostasis, primarily on the important role of hyperphosphatemia. Moreover, vascular calcification has been associated with loss of plasma pyrophosphate, one of the main inhibitors of calcification, thus indicating the importance of the phosphate/pyrophosphate ratio. Extracellular pyrophosphate can be synthesized from extracellular ATP by ecto-nucleotide pyrophosphatase/ phosphodiesterase, whereas pyrophosphate is hydrolyzed to phosphate by tissuenonspecific alkaline phosphatase, contributing to the formation of hydroxyapatite crystals. Over the last decade, vascular calcification has been the subject of numerous reviews and studies, which have revealed new agents and activities that may aid in explaining the complex physiology of this condition. This review summarizes current knowledge about alkaline phosphatase and its role in the process of vascular calcification as a key regulator of the phosphate/pyrophosphate ratio.
Keywords: alkaline phosphatase